Functional Characterization of Pseudoidium neolycopersici Photolyase Reveals Mechanisms Behind the Efficacy of Nighttime UV on Powdery Mildew Suppression - Pathak, Ranjana; Ergon, Åshild; Stensvand, Arne; Gislerød, Hans Ragnar; Solhaug, Knut Asbjørn; Cadle-Davidson, Lance; Suthaparan, Aruppillai (Frontiers in Microbiology, 2020)
Powdery mildews can be controlled by brief exposure to ultraviolet (UV) radiation with devastating effect on their developmental stages including conidia germination. The treatment effect can be impaired by subsequent exposure to UV-A/blue light. UV-A/blue light-activated photolyase may be responsible for this and therefore tested the function of three cryptochrome/photolyase family (CPF)-like genes (OINE01015670_T110144, OINE01000912_T103440 and OINE01005061_T102555) identified in the obligate biotrophic fungus Pseudoidium neolycopersici, the cause of tomato powdery mildew. A photolyase deficient mutant of Escherichia coli transformed with coding sequence of OINE01000912_T103440 and exposed to brief (UV)-C treatment (peak emission at 254 nm) showed photoreactivation and cell survival when exposed to subsequent blue light, indicating complementation of photolyase activity. In contrast, the same photolyase-deficient E. coli transformed with the coding sequences of other two CPF-like genes did not survive this treatment, even though their expression were confirmed at protein level. This confirmed that OINE01000912_T103440 is a gene encoding photolyase, here named PnPHR1, with functionality similar to the native photolyase in E. coli, and classified as a class I CPD photolyases. Modeling of the 634-amino acid sequence of PnPHR1 suggested that it is capable of binding flavin adenine dinucleotide (FAD) and methenyltetrahydrofolate (MTHF). However, spectroscopic data of the protein produced in an E. coli expression system could only reveal the presence of a reduced form of FAD, i.e., FADH¯ as an intrinsic chromophore. Within the tested wavelength range of 365 to 525 nm, the survival of photolyase mutant E. coli transformed with PnPHR1 showed a broad action spectrum from 365 to 454 nm. This was very similar to the previously characterized action spectrum for survival of P. neolycopersici conidia that had been treated with UV-C. Quantitative RT-PCR revealed that the expression of PnPHR1 in P. neolycopersici conidia was induced by UV-C, and peak expression occurred 4 h after brief UV-C treatment. The expression of PnPHR1 was repressed when incubated in red light after the UV-C treatment, but not when incubated in UV-A/blue light. The results may explain why the disease-reducing effect of short wavelength UV is impaired by exposure to UV-A and blue light.